Overpressure Study, Refining Wireling-based Prediction in Southern Pattani Basin, Gulf Of Thailand - Setthaphakdee, Weeranong (Bulletin of Earth Sciences of Thailand, 2021)
The application of Eaton’s sonic log-based pore pressure prediction method is typically the pore pressure analyst’s preferred method for predicting overpressure in the Gulf of Thailand and other hydrocarbon basins in SE-Asia. However, the fracture gradient approach has not yet been used successfully for reliable fracture pressure prediction in this area. Testing the fracture gradient approach and its use in understanding overpressure generation is the focus of this study. Data from ten development wells and two exploration wells from Moragot and Funan fields were used and subjected to Eaton’s sonic-based method for computing pore pressure and fracture gradient were calculated. The results were then compared with RFT log data and LOT measures, respectively. A further comparison using TOC and vitrinite reflection measurements plotted against overpressure across three wells with organic maturation data shows that the onset of overpressure corresponds to the onset of organic maturation. It is likely that the main drivers creating overpressure in the study area are a combination of hydrocarbon generation and variable levels of compaction disequilibrium. The computed overpressure via Eaton’s sonic-based method with an exponential x factor equal to 2 gave the closest result to RFT values showing it can reliably predict overpressure in the Gulf of Thailand. Furthermore, the fracture gradient results show this approach can predict lost circulation zones in wells that had drilling issues. The sonic-based methods produce an estimated pore pressure and fracture trend, which can be useful in areas where pore pressure profiles are not well defined or sediments have experienced depletion pressures, and/or drilling problems (i.e. loss of fluid circulation or fluid influxes). When determining top of overpressure, which will affect porosity and subsurface stress, the application of these methods facilitates an approach of “filling in the gaps”. In addition, in order to minimize drilling risks, this methodology can be reliably employed as the one of techniques utilized while drilling, or in realtime pore pressure estimation (in MWD) and in calculation of mud-weight safety windows.